Seasonal and SARS‐CoV‐2 pandemic changes in the incidence of gestational diabetes - Cauldwell, M (BJOG, 2021)
OBJECTIVE: To test the hypothesis that there is seasonal variation in the rates of gestational diabetes (GDM) diagnosed using a 2‐hour oral glucose tolerance test. DESIGN: Monthly assessment of the percentage of women screened from 1 April 2016 to the 31 December 2020 who were diagnosed as having gestational diabetes. SETTING: London teaching hospital. POPULATION: 28 128 women receiving antenatal care between 1 April 2016 and 31 December 2020. METHODS: Retrospective study of prospectively collected data. MAIN OUTCOME MEASURES: Proportion of women screened diagnosed as having gestational diabetes. RESULTS: The mean (SD) percentage of women diagnosed with GDM was 14.78 (2.24) in summer (June, July, August) compared with 11.23 (1.62) in winter (P < 0.001), 12.13 (1.94) in spring (P = 0.002) and 11.88 (2.67) in autumn (P = 0.003). There was a highly significant positive correlation of the percentage testing positive for GDM with the mean maximum monthly temperature (R (2) = 0.248, P < 0.001). There was a statistically significant 33.8% increase in the proportion of GDM diagnoses from June 2020 onwards, possibly related to a reduction in exercise secondary to the Covid‐19 pandemic. CONCLUSIONS: There is a 23.3% higher rate of GDM diagnoses in the warmer summer months. There has been a 33.8% rise in GDM diagnoses associated with the Covid‐19 pandemic. TWEETABLE ABSTRACT: Rates of GDM are higher in summer and since the onset of the Covid‐19 pandemic.